2001
DOI: 10.1007/bf03033261
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and aluminium effects on the cholinergic system in nerve terminals

Abstract: In the present study, we analyzed how aluminium and oxidative stress induced by ascorbate/Fe(2+) affect the mechanisms related with the cholinergic system in a crude synaptosomal fraction isolated from rat brain. [(3)H]Choline uptake, [(3)H]acetylcholine release, membrane potential and Na(+)/K(+)-ATPase activity were determined in the presence or in the absence of aluminium in control conditions and in the presence of ascorbate (0.8 mM)/Fe(2+) (2.5 micro M). The extent of lipid peroxidation was measured by qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Jyoti et al (2007) have also observed similar changes at the cellular level after Al treatment. Changes in the structure of synapse was also seen after Al treatment, which may affect neurotransmission and hence learning and memory processes in rats and the same is also observed in a number of studies (Rifat et al 1990;Hänninen et al 1994;Amador et al 2001). Al has been shown to alter the cholesterol, phospholipids, total lipids contents of the membranes and thus may be responsible for the membrane damage as seen in an earlier study from our lab ).…”
Section: Discussionsupporting
confidence: 80%
“…Jyoti et al (2007) have also observed similar changes at the cellular level after Al treatment. Changes in the structure of synapse was also seen after Al treatment, which may affect neurotransmission and hence learning and memory processes in rats and the same is also observed in a number of studies (Rifat et al 1990;Hänninen et al 1994;Amador et al 2001). Al has been shown to alter the cholesterol, phospholipids, total lipids contents of the membranes and thus may be responsible for the membrane damage as seen in an earlier study from our lab ).…”
Section: Discussionsupporting
confidence: 80%
“…Various studies have shown that this metal is able to displace Fe in different biomolecules and increase intracellular concentrations of the latter metal thereby promoting the Fenton reaction (Amador et al 2001;Yousef 2004). On the other hand, Al may damage the mitochondrion directly, affecting electron transport in the respiratory chain (Stohs and Bagchi 1995;Bondy and Cambell 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of aluminium, the uptake of neurotransmitters was found to be below control levels, with some exceptions [152,[227][228][229][230][231]. It is interesting to note that aluminium-induced stimulatory effects were only observed when uptake of neurotransmitters was analysed in brain slices [229] or in synaptic plasma membrane vesicles [152].…”
Section: Inactivation Of Neurotransmittersmentioning
confidence: 99%